Bioethics and law - D’Agostino, Francesco (Acta Bioethica, 2002)
This text proposes a series of observations and arguments that allow to suitably locate the challenge raised by bioethics to the law. Kelsen's model consisting in identifying the challenges of bioethics as simple problems of norm content, is postulated as a limited and reductionist approach to the substantial issues that bioethics raises. The way proposed by the author to avoid to turn legal science into a simple technique, would consist in reassuming its specific anthropological validity, which would prevent it from the temptation of sterile formalism, forcing it to work in the perspective of the structures that characterize the being of man, since bioethics addresses general anthropological problems, that are structural problems.